A New Model for Simulating TSS Washoff in Urban Areas - E. Crobeddu; S. Bennis (Applied and Environmental Soil Science)
This paper presents the formulation and validation of the conceptual Runoff Quality Simulation Model (RQSM) that was developed to simulate the erosion and transport of solid particles in urban areas. The RQSM assumes that solid particle accumulation on pervious and impervious areas is infinite. The RQSM simulates soil erosion using rainfall kinetic energy and solid particle transport with linear system theory. A sensitivity analysis was conducted on the RQSM to show the influence of each parameter on the simulated load. Total suspended solid (TSS) loads monitored at the outlet of the borough of Verdun in Canada and at three catchment outlets of the City of Champaign in the United States were used to validate the RQSM. TSS loads simulated by the RQSM were compared to measured loads and to loads simulated by the Rating Curve model and the Exponential model of the SWMM software. The simulation performance of the RQSM was comparable to the Exponential and Rating Curve models.